One-step synthesis of continuous free-standing Carbon Nanotubes-Titanium oxide composite films as anodes for lithium-ion batteries. (1st February 2015) - Gao, Hongxu; Hou, Feng; Wan, Zhipeng; Zhao, Sha; Yang, Deming; Liu, Jiachen; Guo, Anran; Gong, Yuxuan
Graphical abstract: Highlights: CNTs/TiO2 compoiste films synthesized are continuous and free-standing. The film can be directly used as flexible, binder-free Lithium-Ion Battery electrode. The CNTs/TiO2 electrodes exhibit excellent rate capacity and cyclic stability. Our strategy is readily applicable to fabricate other CNTs-based composite films. Abstract: Continuous free-standing Carbon Nanotubes (CNTs)/Titanium oxide (TiO2 ) composite films were fabricated in a vertical CVD gas flow reactor with water sealing by the One-Step Chemical Vapor Deposition (CVD) approach. The composite films consist of multiple layers of conductive carbon nanotube networks with titanium oxide nanoparticles decorating on carbon nanotube surface. The as-synthesized flexible and transferrable composite films show excellent electrochemical properties, when the content of tetrabutyl titanate is 19.0 wt.%, which can be promising as binder-free anodes for Lithium-Ion Battery (LIB) applications. It demonstrates remarkably high rate capacity of 150 mAh g −1, as well as excellent high rate cyclic stability over 500 cycles (current density of 3000 mA g −1 ). Such observations can be attributed to the relatively larger surface area and pore volume comparing with pristine CNT films. Great potentials of CNTs/TiO2 composite films for large-scale production and application in energy devices were shown.